2017
DOI: 10.22159/ijpps.2017v9i3.15866
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Tocotrienol Pretreatment on Ex Vivo Superoxide and Peroxide Handling Capacities (Sphc) of Rat Serum and Brain

Abstract: Objective: Tocotrienol (TT), a constituent of vitamin E, present only in selected seed oil. Because of the isoprenoid side chain, antioxidant property of tocotrienol is recently highlighted. Application of tocotrienol is also proven to be neuroprotective. The current study was aimed to evaluate the effect of tocotrienol pretreatment on the serum and brain oxidative stress parameters and oxidant handling capacities. Methods:Male albino Wistar rats were treated with tocotrienol (10 mg/day) for two weeks and main… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 18 publications
2
6
0
Order By: Relevance
“…The larvae fed on diet supplemented with AB when allowed to develop into adults maintained on normal diet also show a decrease in total GSH content as compared to control flies, throughout the span of 40 days. It has been reported that increase in GSH content leads to a proportionate increase in antioxidant capacity of an organism [29][30][31]. In the current study, it has been noticed that even with low concentration of GSH, the intrinsic GSH:GSSG ratio remains unaltered in flies from AB-supplemented regimes.…”
Section: Discussionsupporting
confidence: 46%
“…The larvae fed on diet supplemented with AB when allowed to develop into adults maintained on normal diet also show a decrease in total GSH content as compared to control flies, throughout the span of 40 days. It has been reported that increase in GSH content leads to a proportionate increase in antioxidant capacity of an organism [29][30][31]. In the current study, it has been noticed that even with low concentration of GSH, the intrinsic GSH:GSSG ratio remains unaltered in flies from AB-supplemented regimes.…”
Section: Discussionsupporting
confidence: 46%
“…This was in accordance with our earlier observation where the same dose of T3 showed significant changes in body weight. [23] The percentage changes in body weight, in the current study, were also influenced significantly by the Et exposures in all the groups except PT3. Therefore, even in the absence of overall change in absolute body weight, the currently used low-to-moderate doses of Et exposure was sufficient to contribute significantly in the slowing of body weight gain.…”
Section: Discussionsupporting
confidence: 57%
“…Maintenance of systemic, organ or regional GSH level by vitamin E, TRF or T3 in presence of oxidative stressor had been reported times and again. [23,32,[37][38][39][40][41][42] Increases in cerebellar GSH level were noticed in the ST3 group (statistically significant) and TT3 group (statistically significant) in comparison to NT3 and PT3 groups of Et-0 phase of current study. However, in presence of Et exposures, TT3 group abled to maintain the level of cerebellar GSH while ST3 group failed to do so.…”
Section: Biochemical Parametermentioning
confidence: 51%
“…A high intake of antioxidants may decrease the risk of colon cancer and prevent the metastases [1][2][3]. One of the antioxidant sources naturally abundant is tocopherol and tocotrienol or Vitamin E which is soluble in water [4]. However, Vitamin E degrades easily by chemical or physical action during storage or when it is delivered to the appropriate site of action after ingestion [5].…”
Section: Introductionmentioning
confidence: 99%